THE ROLE OF E-BOOK IN ENHANCING SIMPLE PAST TENSE LEARNING FOR ELEMENTARY STUDENTS - Tama, Anggi Ade Tiya; Misrita, Misrita; Putri, Librina Tria (Journal Compound: Improving the Quality of English Education, 2024)
The study focused on the role of an e-book as an effective teaching tool for enhancing elementary-level students’ understanding and usage of the simple past tense in English. The primary objective was to examine how interactive digital resources—such as audio recordings, visual aids, animations, and embedded practice exercises—could support language acquisition by catering to diverse learning styles, including auditory, visual, and kinesthetic learners. The e-book was designed to provide clear explanations, examples, and exercises on the simple past tense, allowing students to learn at their own pace in a self-directed manner. This research method involved how to applied electronic books as teaching materials in students’ especially in using the simple past tense in spoken and written English. The findings indicated that the use of the e-book as a teaching tool gave a motivation for students in learning simple past tense, while also fostering greater engagement and motivation in the learning process.